Production and diversity analysis of cellulases from Anoxybacillus genus - RAHMAT EKO SANJAYA; NI NYOMAN TRI PUSPANINGSIH; ALI ROHMAN; HAKIKI RAHMASARI; ROSLI MD. ILLIAS; NAWEE JANTARIT; KAZUHITO FUJIYAMA; ANDRE PRATAMA; FATIHA KHAIRUNNISA (Society for Indonesian Biodiversity, 2024)
Abstract. Sanjaya RE, Puspaningsih NNT, Rohman A, Rahmasari H, Illias RM, Jantarit N, Fujiyama K, Pratama A, Khairunnisa F. 2024. Production and diversity analysis of cellulases from Anoxybacillus genus. Biodiversitas 25: 2705-2718. Bioconversion of cellulose into sustainable renewable resources of oligosaccharides and glucose requires cellulase action. Genomic sequences of Anoxybacillus cellulases are available in GenBank databases, but no information about their biochemical properties. Anoxybacillus flavithermus TP-01 is a thermophilic, facultatively anaerobic, cellulase-producing bacterium isolated from the mountain of Gunung Pancar hot springs, Bogor, Indonesia. This study aimed to characterize the cellulase produced by Anoxybacillus flavithermus TP-01, a local Indonesian isolate. This cellulase was characterized and the diversity analysis on biochemical properties and structural characteristics was done by in silico approaches. SOPMA, SWISS-MODEL, I-TASSER, ProSA, and SAVES were used for computational analysis on physicochemical characterization, phylogenetic construction, functional analysis, multiple sequence alignment, and secondary-tertiary structure prediction. Physicochemical analysis showed pI<7, indicating acidic property for these proteins. Furthermore, the proteins were thermostable and hydrophilic, as proved by their relatively high aliphatic index and negative GRAVY values. The five sequence motifs harbored a conserved domain of the M42 peptidase/endoglucanase family. Alpha helix was the predominant secondary structure, and the tertiary structure fulfilled the structural quality criteria of QMEAN4, ERRAT, Ramachandran plot, and Z-score. Structural comparison between the template structure and the models revealed significant differences in the loop sections. This study identified a potentially thermostable cellulase of Anoxybacillus flavithermus TP-01, and provided new insights of the physicochemical, functional, and explores the structure-function relationship of cellulase from Anoxybacillus genus based on in silico data.